Secure fixation of femoral bone plug with a suspensory button in anatomical anterior cruciate ligament reconstruction with bone-patellar tendon-bone graft - Taketomi, Shuji; Inui, Hiroshi; Nakamura, Kensuke; Yamagami, Ryota; Tahara, Keitaro; Sanada, Takaki; Masuda, Hironari; Tanaka, Sakae; Nakagawa, Takumi (Joints, 2015)
Purpose: the efficacy and safety of using a suspensory button for femoral fixation in anatomical anterior cruciate ligament (ACL) reconstruction with bonepatellar tendon-bone (BPTB) graft have not been established. The purpose of the current study was to evaluate bone plug integration onto the femoral socket and migration of the bone plug and the EndoButton (EB) (Smith & Nephew, Andover, MA, USA) after rectangular tunnel ACL reconstruction with BPTB autograft.Methods: thirty-four patients who underwent anatomical rectangular ACL reconstruction with BPTB graft using EB for femoral fixation and in whom three-dimensional (3D) computed tomography (CT) was performed one week and one year after surgery were included in this study. Bone plug integration onto the femoral socket, bone plug migration, soft tissue interposition, EB migration and EB rotation were evaluated on 3D CT. The clinical outcome was also assessed and correlated with the imaging outcomes.Results: the bone plug was integrated onto the femoral socket in all cases. The incidence of bone plug migration, soft tissue interposition, EB migration and EB rotation was 15, 15, 9 and 56%, respectively. No significant association was observed between the imaging outcomes. The postoperative mean Lysholm score was 97.1 ± 5.0 points. The postoperative side-to-side difference, evaluated using a KT-2000 arthrometer, averaged 0.5 ± 1.3 mm. There were no complications associated with EB use. Imaging outcomes did not affect the postoperative KT side-to-side difference.Conclusions: the EB is considered a reliable device for femoral fixation in anatomical rectangular tunnel ACL reconstruction with BPTB autograft.Level of evidence: Level IV, therapeutic case series.
Keywords: anterior cruciate ligament reconstruction; bone-patellar tendon-bone; EndoButton; suspensory fixation